Training to Improve Teacher's Competency in Developing Class Action Research Proposals Through a Participatory Training Model with Intensive Assistance - Corry Yohana; Mardi; Sri Indah Nikensari; Riski Firdausi Rachmadania; Susan Febriantina (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2022)
The purpose of this service activity is to provide participants with understanding and knowledge about the importance of making classroom action research, as well as increase the enthusiasm of teachers to make CAR and implement CAR as expected so teachers do not experience problems in writing CAR reports because Classroom Action Research is seen as a form of research. the most appropriate improvement in the quality of learning. The method uses training with a participatory training model and intensive mentoring, Data collection techniques use interviews to obtain data about the difficulties of teachers in preparing CAR proposals, observations to observe the implementation of the participatory training model with intensive mentoring, and evaluation of CAR proposals to obtain data on the success of model implementation. training. The implementation of this training was attended by 65 teachers. With this training, teachers have knowledge and insight as skilled teachers because apart from being researchers, teachers also act as PBM implementers so that they know very well the problems they are facing, and the conditions to be achieved.